Are Passive Physical Modalities Effective for the Management of Common Soft Tissue Injuries of the Elbow?: A Systematic Review by the Ontario Protocol for Traffic Injury Management (OPTIMa) Collaboration. Issue 1 (January 2017) - Dion, Sarah; Wong, Jessica J.; Côté, Pierre; Yu, Hainan; Sutton, Deborah; Randhawa, Kristi; Southerst, Danielle; Varatharajan, Sharanya; Stern, Paula J.; Nordin, Margareta; Chung, Chadwick; D'Angelo, Kevin; et al.
Abstract : Objective: To evaluate the effectiveness of passive physical modalities for the management of soft tissue injuries of the elbow. Methods: We systematically searched MEDLINE, EMBASE, CINAHL, PsycINFO, and Cochrane Central Register of Controlled Trials from 1990 to 2015. Studies meeting our selection criteria were eligible for critical appraisal. Random pairs of independent reviewers critically appraised eligible studies using the Scottish Intercollegiate Guidelines Network criteria. We included studies with a low risk of bias in our best evidence synthesis. Results: We screened 6618 articles; 21 were eligible for critical appraisal and 9 (reporting on 8 randomized controlled trials) had a low risk of bias. All randomized controlled trials with a low risk of bias focused on lateral epicondylitis. We found that adding transcutaneous electrical nerve stimulation to primary care does not improve the outcome of patients with lateral epicondylitis. We found inconclusive evidence for the effectiveness of: (1) an elbow brace for managing lateral epicondylitis of variable duration; and (2) shockwave therapy or low-level laser therapy for persistent lateral epicondylitis. Discussion: Our review suggests that transcutaneous electrical nerve stimulation provides no added benefit to patients with lateral epicondylitis. The effectiveness of an elbow brace, shockwave therapy, or low-level laser therapy for the treatment of lateral epicondylitis is inconclusive. We found little evidence to inform the use of passive physical modalities for the management of elbow soft tissue injuries. Abstract : Supplemental Digital Content is available in the text.